Development of Integrated Learning Programs in Chemical Thermodynamics : Final Report fro a 1994 National Teaching Development Grant. - Lee, Hae-Geon (Committee for the Advancement of University Teaching, 1994)
Final report from a project that developed a computer aided learning package in chemical thermodynamics. The package covers from the fundamental level to the advanced applications for minerals, metals and materials. It provides a comprehensive treatment of all important topics of thermodynamics. Each topic is presented in the same way as a lecturer teaches in the class. Added benefit is that a student may freely select and repeat a topic of interest. The package is structured to be interactive and self-guided so that it has implications for improving not only undergraduate engineering education but also the provision of post-graduation professional training.